Mapping Digital Business Innovation: A Bibliometric Analysis of SDG Integration - Yuhefizar, Yuhefizar; Watrianthos, Ronal (Politeknik Negeri Bengkalis, 2024)
This study investigates how research in digital business innovation has evolved to incorporate sustainabilityobjectives through a systematic analysis of academic literature from 2016 to 2024. The research employs a comprehensivebibliometric approach to analyze 1,627 documents from 684 sources in the Scopus database, focusing on publicationpatterns, thematic evolution, and emerging research directions. The analysis reveals three distinct phases in the field's development: foundation (2016-2018), integration (2019-2021), and transformation (2022-2024). Publication volumesshow significant growth from 7 articles in 2016 to 482 in 2024, with a marked acceleration following the COVID-19pandemic. Research themes cluster around three main areas: digital business innovation (572 publications), economicstability (245 publications), and sustainability implementation (156 publications). Core integration themes focus onenvironmental, social, and governance (ESG) implementation and green innovation, while emerging areas emphasizeartificial intelligence applications and circular economy principles. The findings demonstrate a clear shift from technologyfocused approaches to integrated frameworks that align digital transformation with sustainability goals. Analysis ofresearch patterns reveals increasing emphasis on ESG integration (16.8% of recent publications) and sustainable businessmodels, though significant gaps remain in standardization and long-term impact measurement. This study contributes tounderstanding how organizations can effectively combine digital innovation with sustainability objectives, highlightingopportunities for future research in measurement frameworks and ethical implementation guidelines.